Is Primary Opening of Fistula-in-Ano Always at Dentate Line: Correlation Between MRI and Operative Findings in 379 Patients - Garg P; Naldini G; De Parades V; Tsarkov P; Yagnik VD; Bhattacharya K; Kaur B; Mahak G (Clinical and Experimental Gastroenterology)
Pankaj Garg,1 Gabriele Naldini,2 Vincent De Parades,3 Petr Tsarkov,4 Vipul D Yagnik,5 Kaushik Bhattacharya,6 Baljit Kaur,7 G Mahak8 1Department of Colorectal Surgery, Garg Fistula Research Institute, Panchkula, Haryana, 134113, India; 2Director of Proctology and Pelvic Floor Multidisciplinary Clinical Center, San Rossore Private Hospital Pisa, Pisa, 56127, Italy; 3Department of Medico Surgical Proctology, Institut Léopold Bellan, Hospital Paris Saint Joseph, Paris, 75674, France; 4Professor & Head, Department of Colorectal Surgery, Sechenov First Moscow State Medical University, Moscow, 119991, Russian Federation; 5Professor, Department of Surgery, Banas Medical College and Research Institute, Palanpur, Gujarat, 385001, India; 6Associate Professor, Department of Surgery, MGM Medical College and LSK Hospital, Kishanganj, Bihar, 855107, India; 7Department of MRI Imaging, SSRD MRI Center, Chandigarh, 160011, India; 8Chief Research & Scientific Officer, Garg Fistula Research Institute, Panchkula, Haryana, 134113, IndiaCorrespondence: Pankaj Garg, CEO & Chief Colorectal Surgeon, Garg Fistula Research Institute, 1042, Sector-15, Panchkula, Haryana, 134113, India, Fax +0091-9501011000, Email drgargpankaj@yahoo.comBackground: The primary opening of the cryptoglandular fistula-in-ano is generally assumed to be present at the dentate line as the cryptoglandular glands open there. However, no study has ever systematically studied the location of the primary opening.Methods: All fistula-in-ano patients operated-on over two years were screened and those who were never earlier operated on were included. Magnetic Resonance Imaging (MRI) was done on all patients. The primary fistula opening was localized on the MRI and corroborated with the operative findings. The primary opening was categorized at three levels - at the dentate line, above the dentate line, and below the dentate line.Results: 744 anal fistula patients were operated on over two years and 379 patients, who had never been operated on before, were included in the study. 35 patients were excluded (the primary opening could not be localized). In 344 patients (finally analyzed), the primary opening was at the dentate line in 223 patients (64.8%), above the dentate line in 79 (22.9%), and below the dentate line in 42 (12.2%) patients. The primary opening was located above the dentate line in significantly higher numbers in complex fistulas than in simple fistulas (73/102 in complex vs 6/242 in simple fistulas, p< 0.00001).Conclusion: Unlike commonly presumed, the primary opening is located at the dentate line in only two-thirds (64.8%) anal fistulas. In 22.9% it was located above the dentate line and in 12.2%, below the dentate line. This is the first study in which the level of primary opening has been systematically analyzed.Keywords: rectal fistula, anal fistula, MRI, internal opening, primary opening, dentate line